Prevalence and attitudes associated with the use of electronic cigarettes among university students in the Northeastern region of Brazil - Carneiro Portela, Sarah; Guimarães Marques da Silva, Taís; Barbosa Venâncio Alencar, Eduarda; Gadelha de Castro, Maria Darlyele; Pinheiro Ferreira da Silva, Guilherme (Fisioterapia & Saúde Funcional, 2025)
Objective: Assess the prevalence and attitudes associated with the use of electronic cigarettes in college students in the Northeastern region of Brazil. Methods: A cross-sectional study was conducted on the campus of the University of Fortaleza (UNIFOR) from February to March 2023. The study population consisted of 300 regularly enrolled students from the four UNIFOR Science Centers, aged 18 years and above, who agreed to participate in the research by electronically signing the Informed Consent Form. Participants were recruited through on-campus approaches, invitations made by the researchers, and through social media promotion. The data collection instrument was made available through a link to the research instrument created by the authors using Google Forms®, containing questions that addressed sociodemographic data and tobacco-related attitudes. Results: The prevalence of e-cigarette use was 24% (n=72). Most of the sample-initiated e-cigarette use upon entering the university environment (n=38; 52.8%), with a predominance in the age group of 16-20 years (n=53; 73.6%), and a frequency of daily use (n=25; 34.7%), as well as social use (n=22; 30.6%). Furthermore, the main reasons for starting to use were curiosity and the influence of friends/peers (71.4% and 56%, respectively). Conclusions: The prevalence of e-cigarette use among university students in the study was 24%.